Propensity toward indebtedness: a bibliometric analysis of research trends and clusters - Mohd Yusoff, Yuslizawati; Tan, Yan Ling; Tay, Bee Hoong; Elias@Alias, Suhaidi; Othman, Nor Azairiah Fatimah (UiTM Cawangan Johor, 2025)
This study offers a comprehensive bibliometric examination of the research field surrounding the concept of predisposition for indebtedness. Based on articles indexed in major academic databases, significant trends, influential authors, leadingjournals, and topic clusters that have historically affected the discipline were explored. The study used co-citation, keyword co-occurrence, and bibliographic coupling to elucidate the interdisciplinary character of the topic, encompassing domains such as behavioural economics, consumer finance, psychology, and social policy. The findings showed that there was a shift in priorities of debt-related research on the issues of credit behaviour, financial literacy, debt-related stress, and socio-demographic characteristics that influence indebtedness. Furthermore, the analysis revealed critical areas of investigation and prospective deficiencies for subsequent exploration. This bibliometric method delineates the conceptualframework ofthe discipline while offering significant insights for scholars, policymakers, and practitioners focused on comprehending and tackling the behavioural determinants of debt. Keywords: Indebtedness, behavioral economics, bibliometric analysis